The rise of Iskandar Malaysia: implications for Singapore’s marine and coastal environment - Cook, Alistair David Blair (2018)
Iskandar Malaysia, a major economic zone in the southern part of Malaysia, is experiencing meteoric growth. Given that the zone lies along the Straits of Johor, how will the increasing industrialisation and urbanisation seen in the area affect the marine and coastal environment? Also, what are the implications of this growth for Singapore, whose northern coast lies on the other side of the Straits? This NTS Insight investigates these questions and suggests ways to mitigate the potential impacts of developments in Iskandar Malaysia on Singapore’s marine and coastal environment.